'We're in the coal business': Maintaining fossil fuel hegemony in the face of climate change. (September 2022) - Wright, Christopher; Irwin, Randi; Nyberg, Daniel; Bowden, Vanessa
Despite the worsening climate crisis and market shifts towards decarbonization, Australia remains heavily invested in carbon-intensive activities. As one of the world's largest exporters of coal and gas, Australian political economy has been dominated over the last several decades by fossil fuel expansionism. In this article, we explore how Australian corporate and political elites have defended the continuation of fossil fuel extraction and use in the face of calls for a transition to a low-carbon energy future. Through an analysis of public statements by industry associations, corporate leaders, politicians and trade union officials, we identify how these actors have constructed a hegemonic temporal narrative stressing the historical importance of fossil fuels and that a transition to renewable energy represents a threat to Australia's future. Our analysis contributes to the growing literature within the field of industrial relations attending to the complex industrial dynamics underlying the maintenance of fossil fuel hegemony. We also contribute to recent discussions on hegemony by demonstrating the importance of temporality in linking diverse actors together in defending hegemony. Finally, we highlight the critical importance of corporate power in fundamentally shaping climate and energy politics.